2003
DOI: 10.1093/annonc/mdg055
|View full text |Cite
|
Sign up to set email alerts
|

Optimum trephine length in the assessment of bone marrow involvement in patients with diffuse large cell lymphoma

Abstract: Morphological bone marrow involvement in DLCL is optimally demonstrated by a 20-mm long trephine biopsy from a single site which is examined at multiple levels (four or more). This obviates the need for bilateral sampling, thereby reducing patient morbidity from the procedure. This study provides evidence to support the National Cancer Institute recommendations regarding trephine biopsy in the staging of DLCL, providing multiple levels are examined.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
49
1

Year Published

2003
2003
2012
2012

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(54 citation statements)
references
References 19 publications
4
49
1
Order By: Relevance
“…It was previously believed that bilateral trephine biopsies increased the yield from staging BMs in NHL (Juneja et al 1990). However, it is now established that bilateral sampling is not required if adequate tissue (including adequate trephine length and number of levels examined) is available for diagnosis (Campbell et al 2003). Our mean trephine length was reasonable at 17.6 mm, with a range of 8-36 mm.…”
Section: Discussionmentioning
confidence: 69%
See 3 more Smart Citations
“…It was previously believed that bilateral trephine biopsies increased the yield from staging BMs in NHL (Juneja et al 1990). However, it is now established that bilateral sampling is not required if adequate tissue (including adequate trephine length and number of levels examined) is available for diagnosis (Campbell et al 2003). Our mean trephine length was reasonable at 17.6 mm, with a range of 8-36 mm.…”
Section: Discussionmentioning
confidence: 69%
“…Two examples where discrete populations of large B cells were noted on immunostaining that were not apparent on careful review of routine histology slides are shown in Figure 3. A previous study by Campbell et al (2003) established that four levels is the optimal number that need to be examined for routine morphological assessment in staging DLBCL. A similar study is required to assess how much of the benefit obtained on immunostaining is caused by examination of multiple levels.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, assessment of marrow involvement by histology is not impeded by fibrosis, which is a frequent finding in lymphomatous infiltrates and may lead to false-negative results in BM aspirates due to sampling error [8][9][10] . For these reasons, the performance of a unilateral (or bilateral) BM trephine of adequate size with a minimal length of 2 cm, preferably examined by step sectioning, is regarded mandatory in patients with malignant lymphoma both for the initial determination of BM involvement and response evaluation [11,12] . However, trephine biopsy, aspiration cytology and flow cytometric immunophenotyping should be seen as integral parts of a combined approach ideally resulting in a joint diagnostic assessment [1,3] .…”
Section: Introductionmentioning
confidence: 99%